REVITALISASI BUDAYA AKADEMIK SEKOLAH MELALUI PROGRAM PELATIHAN PENULISAN KARYA ILMIAH DASAR BAGI SISWA SMAS GUPPI GOWA - Eka Fitriana Hamsyah; Nur Amaliah Akhmad1; andi nur samsi; gustina; Irnayanti Bahar5 (Amaliah: Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service program aimed to enhance students’ scientific literacy competence through basic scientific writing training at SMAS GUPPI Gowa. The program was implemented systematically in three stages: planning, implementation, and evaluation, using a participatory and applicative approach. The planning stage included an initial assessment (pre-test), needs analysis, and the development of training modules covering the structure of scientific papers, problem formulation, simple literature review, basic research methods, and citation techniques. The implementation phase was conducted through interactive project-based workshops combined with hands-on drafting practice and intensive mentoring via writing clinics. Evaluation was carried out by comparing pre-test and post-test results and assessing the quality of students’ draft papers. The findings revealed a significant improvement in students’ understanding, increasing from 36% to 64% in conceptual aspects and from 28% to 88% in structural understanding. Furthermore, the quality of students’ writing improved in terms of organization, coherence, and formatting accuracy. The program proved effective in strengthening scientific literacy and fostering a sustainable academic culture within the school.